Hey there! I'm happy to help!
To solve by substitution, rearrange one of the equations for one of the variables.
3x+2y=11
Subtract 2y from both sides.
3x=11-2y
Divide both sides by 3.
x=11/3-2/3y
Now we plug this value of x into the second equation to solve for y.
2(11/3-2/3y)-2y=14
We use distributive property to undo the parentheses.
22/3-4/3y-2y=14
We combine like terms.
22/3-10/3y=14
We subtract 22/3 from both sides.
-10/3y=20/3
Divide both sides by -10/3.
y=-2
We plug this value into one of the equations to solve for x.
3x+2(-2)=11
3x-4=11
Add 4 to both sides.
3x=15
Divide both sides by 3.
x=5
So, the solution is x=5 and y=-2 or (5,-2).
Have a wonderful day! :D